Leading change and innovation in higher education : a case study of open and distance learning institution in Nigeria - Akinbode, Akintola Ismaila (Kulliyyah of Education, International Islamic University Malaysia, 2021)
This research investigated how change initiatives and technological innovation are being initiated and implemented in Higher Education Institutions with special reference to Open and Distance Learning (ODL) institution and a case study of National Open University of Nigeria (NOUN). The institution is a federal Open and Distance Learning (ODL) institution in Nigeria which provides educational access to teeming youths and adults across the country. The study adopted qualitative approach to explore change initiatives recently implemented in the institution. The research also investigated the strategies adopted by the educational leaders of National Open University of Nigeria to implement the recent technological innovation and challenges faced during the implementation process. Eight participants which included administrators, centre coordinators, ICT experts, and lecturers were purposely selected for interview, while focus group discussion was conducted with ten students from various levels of the study in the institution. Documents analysis was adopted in conjunction with the interview to compare and contrast the data collected. Thematic method was used to analyse the data. The study revealed that the recent change initiatives in Open and Distance Learning Institution cut across different areas such as technology tools modification, course modification (OER, MOCC), staff development and shifting to internal data management. The reasons identified for various change initiatives included technology explosion, provision of cost effective and quality education, supporting UNESCO initiative of education for all, enabling access to education for all knowledge seekers in the country, most especially youth who do not have the opportunity to be absorbed into the conventional universities, meeting the need of the students and staff, and host of others. The strategies adopted for the change process covered all phases of the implementation process starting from the pre-implementation to post-implementation stage. The challenges faced during the change process include fear of changes, learning institutions and students becoming victims of data management providers, poor understanding of people, strategic issue, data migration challenges and time frame. The study also discovered that there was poor communication during the change process which caused anxiety and resistance; some of the functions of the new LMS were not properly working and students' enquiries through the LMS were not promptly replied. In addition, the study found out that change processes did not sequentially follow classical change theory, Kurt Lewin change theory, but rather moved within the spectrum of classical and contingency models. The recommendations for the present change initiative include upgrading of the new LMS to suit the students' needs, answering the queries posted by students in the LMS urgently, ensuring that all the functions in the LMS are working properly, provision of up-to-date training for the technical teams that are handling the system and ensuring that non-stop orientation and communication are provided for the students and the general public.